The experiences of Chinese colorectal cancer survivors in marital intimacy after ostomy creation: A qualitative study - Du, Xixi; Chaiviboontham, Suchira; Sumdaengrit, Bualuang (Belitung Raya Foundation, Indonesia, 2024)
Background: Colorectal cancer (CRC) ranks as the third most prevalent cancer globally. The disease and its treatment significantly impact marital intimacy, particularly among individuals who have undergone ostomy creation. Therefore, it is necessary to explore their experiences. Objective: This study aimed to explore the experiences of colorectal cancer survivors in marital intimacy after ostomy creation and clarify the domain and sub-domain of marital intimacy in CRC survivors with ostomy. Method: This study used a qualitative descriptive design, and participants were selected by purposive sampling from two hospitals in Henan province, China. Sixteen patients participated in this research, and the data were collected through an in-depth interview from June 27 to September 27, 2023. Colaizzi’s method was used to analyze the data. Results: Five themes emerged from data analysis, including physical intimacy, psychological intimacy, social intimacy, spiritual intimacy, and operational intimacy. Conclusion: By profiling the experiences of CRC survivors in marital intimacy after ostomy creation, the domain and sub-domain of marital intimacy were clarified in this cohort and revealed that ostomy had a severe effect on marital intimacy among colorectal cancer survivors. The results from this study could be used by nurses, midwives, and other healthcare professionals to design specific interventions covering all aspects of marital intimacy. Also, the findings will guide the development of a particular instrument for marital intimacy in CRC survivors with ostomy.